PENGGUNAAN EKSTRAK BIOTA LAUTAGLAOPHENIA SP. UNTUK MENGENDALIKANFUSARIUM OXYSPORUM F.SP.VANILLAE PENYEBAB BUSUK BATANG VANILI - SUADA, I KETUT (Agrotrop : Journal on Agriculture Science; Vol 1 No 1 (2011))
The Use of Aglaophenia sp. Marine Biota Extract to Control Fusarium oxysporum f. sp. vanillae, a Pathogen of Vanilla Stem Rot The use of marine biota for organic fungicide material has enormous potential to be developed. The organic fungicide was directed to substitute synthetic fungicide for vanilla cultivation. Application of synthetic fungicide degraded environmental quality, therefore its applications does not support sustainable agriculture. The objective of this research was to know the potence of Aglaopheniain suppressing the growth of F. oxysporum f. sp.vanillae, the pathogen of vanilla stem rot. The research was done in green house in order to find the best substance for formulation of the extract. The substances screened were water, tween-80, and detergents with two different concentrations. Subsequently, two best formulas were chosen to apply in endemic area in Tabanan. The green house and field trial research used Randomized Completely Design with three and five replications respectively. Results showed that tween was the best substance used for formulation and concentration of 0.2% was better than other concentrations. The extract diluted in tween-80 on the concentration of 0.2% showed the lowest rot on stem, longest shoot, and the most leaves on vanilla shoot. Because of its significant performance, the 0.1% extract ofAglaopheniain 0.1% tween-80 was proposed to be the best formula to suppress the vanilla stem rot disease.
Keywords: Aglaophenia sp., vanilla stem rot